Elevated Neutrophil to Lymphocyte Ratio Associated With Increased Risk of Recurrent Vascular Events in Older Minor Stroke or TIA Patients - Chan, Ka Lung; Feng, Xueyan; Ip, Bonaventure; Huang, Shangmeng; Ma, Sze Ho; Fan, Florence S. Y.; Ip, Hing Lung; Huang, Li’an; Mok, Vincent C. T.; Soo, Yannie O. Y.; Leung, Thomas W.; Leng, Xinyi (Frontiers in Aging Neuroscience, 2021)
Background The risk of recurrent stroke following a minor stroke or transient ischemic attack (TIA) is high, when inflammation might play an important role. We aimed to evaluate the value of neutrophil to lymphocyte ratio (NLR) in predicting composite cardiovascular events in patients with minor stroke and TIA. Methods Consecutive patients with acute minor stroke or TIA admitted within 24 h of symptoms onset during a 5-year period in a prospective stroke registry were analyzed. We calculated the NLR dividing absolute neutrophil count by absolute lymphocyte count tested within 24 h of admission. NLR ≥4th quartile was defined as high NLR. A composite outcome was defined as stroke, acute coronary syndrome or vascular death within 1 year. We investigated associations between NLR and the composite outcome in univariate and multivariate analyses, among all patients and in those aged over 60 years (i.e., older patients). Results Overall, 841 patients (median age 68 years; 60.4% males) were recruited. No significant independent association was found between NLR and the composite outcome in multivariate analysis in the overall cohort. Among the 612 older patients (median age 73 years; 59.2% males), the median NLR was 2.76 (interquartile range 1.96−4.00) and 148 (24.2%) patients had high NLR. The composite outcome occurred in 77 (12.6%) older patients, who were more likely to have a high NLR (39.0% versus 22.1%; p = 0.001) than those without a composite outcome. In multivariate logistic regression, high NLR (adjusted odds ratio 2.00; 95% confidence interval 1.07−3.75; p = 0.031) was independently associated with the composite outcome in older patients. Conclusion In older (aged ≥60 years) patients with acute minor stroke or TIA, a higher NLR, a marker of systemic inflammation that can be easily obtained in routine blood tests, is an independent predictor of subsequent cardiovascular events.